Biological responses to change in Antarctic sea ice habitats - Swadling, Kerrie M.; Constable, Andrew J.; Fraser, Alexander D.; Massom, Robert A.; Borup, Melanie D.; Ghigliotti, Laura; Granata, Antonia; Guglielmo, Letterio; Johnston, Nadine M.; Kawaguchi, So; Kennedy, Fraser; Kiko, Rainer; et al. (Frontiers in Ecology and Evolution, 2023)
Sea ice is a key habitat in the high latitude Southern Ocean and is predicted to change in its extent and duration in coming decades. The sea-ice cover is instrumental in mediating ocean-atmosphere exchanges and provides an important substrate for organisms from microbes to predators. Antarctic krill, Euphausia superba, are reliant on sea ice during key phases of its life cycle, particularly during the larval stages, as feeding grounds and refuge from their predators, while other small grazers, including copepods and amphipods, either live in the brine channel system or find food and shelter at the ice-water interface and in rafted pockets. Fish, such as the Antarctic silverfish Pleuragramma antarcticum, use platelet ice (loosely-formed frazil crystals) as an essential hatchng and nursery ground. In this paper, we apply the framework of the Marine Ecosystem Assessment for the Southern Ocean (MEASO) to review current knowledge about relationships between sea-ice coverage and associated primary production and secondary consumers. We then use qualitative network modelling to explore possible responses of sea-ice biota to different perturbations, including warming air and ocean temperatures, increased storminess and reduced annual sea-ice duration. This modelling shows that pelagic algae, copepods, krill and fish are likely to decrease in response to warming temperature and reduced sea-ice duration, while salp populations will likely increase under conditions of reduced sea-ice duration and increased number of days greater than 0 oC. Differences in responses to these pressures between the five MEASO sectors were also explored. Greater current impacts of environmental pressures on ice-related biota were found for the Western and Eastern Pacific (notably the Ross Sea and western Antarctic Peninsula), with likely flow-on effects to the wider ecosystem, and smaller responses in the other sectors. All sectors are expected to be impacted over coming decades. Finally, we highlight priorities for future sea ice biological research to address knowledge gaps in this field.